Busy O'Brien and the great bubble gum blowout - Poploff, Michelle (New York : Walker and Co., 1990)
Ten-year-old Busy O'Brien tries to raise funds for the town's Meal Mobile by organizing the Great Bubblegum Blowout.
9 13 19 38
Keywords: City and town life -- Fiction; Bubble gum -- Fiction; Moneymaking projects -- Fiction